Primary Gastric Burkitt Lymphoma: An Unusual Diagnosis for a Common Symptom - Rogalidou, Maria; Avgerinou, Georgia; Stefanaki, Kalliopi; Patereli, Amalia; Gavra, Maria; Georgiadou, Elissavet; Kattamis, Antonis; Papadopoulou, Alexandra (Archives of Clinical and Biomedical Research, 2025)
Non-Hodgkin lymphomas (NHLs) account for about 4% of malignancies in children younger than 15 years old [1]. Burkitt lymphoma (BL) is an aggressive non-Hodgkin B cell lymphoma, characterized by the translocation of the MYC oncogene [2]. Intermittent epigastric pain and vomiting are common symptoms in children and adolescents, and in most cases no special further investigations are required. Proton pump inhibitors are often prescribed as an initial measure to relieve symptoms. However, if symptoms persist or are accompanied by other findings such as anemia or weight loss, further investigation is required and, surprisingly, a very rare disease may be the final diagnosis. Primary non-Hodgkin's lymphoma (NHL) of the gastrointestinal tract is the most common extranodal lymphoma in children [3]. However, primary gastric NHL is rare in children [4] and accounts for less than 2% of pediatric NHL cases [5]. Burkitt lymphoma (BL) is a common type of NHL, but gastric BL usually occurs in older people, while it is very rare in children [6].